2015
DOI: 10.1039/c5ra18966g
|View full text |Cite
|
Sign up to set email alerts
|

Variable corrosion behavior of a thick amorphous carbon coating in NaCl solution

Abstract: The present work investigates a thick amorphous multi-layer carbon coating fabricated by a plane hollow cathode plasma-enhanced chemical vapor deposition technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…When performed in the aggressive seawater solution, the coatings containing alternating interface and few pinhole layers exhibited good corrosion resistance due to its better ability of corrosion prevention. This was similar to the multilayer coatings, in which the corrosion resistance improvements were not only attributed to the reduced possibility of media throughout coatings by defects but also redirected the current flow between coatings and substrates . Furthermore, the high adhesion strength also contributed to the high anti‐corrosion performance of coatings.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…When performed in the aggressive seawater solution, the coatings containing alternating interface and few pinhole layers exhibited good corrosion resistance due to its better ability of corrosion prevention. This was similar to the multilayer coatings, in which the corrosion resistance improvements were not only attributed to the reduced possibility of media throughout coatings by defects but also redirected the current flow between coatings and substrates . Furthermore, the high adhesion strength also contributed to the high anti‐corrosion performance of coatings.…”
Section: Discussionsupporting
confidence: 62%
“…This was similar to the multilayer coatings, in which the corrosion resistance improvements were not only attributed to the reduced possibility of media throughout coatings by defects but also redirected the current flow between coatings and substrates. [40] Furthermore, the high adhesion strength also contributed to the high anti-corrosion performance of coatings. Otherwise, the further increase of intermediate plasma treatments would induce grain refinement, which implied that more grain boundary could provide more paths for the corrosive electrolyte to access the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, BN and graphite coatings showed relatively smaller semicircles. The larger the semicircle, the higher the charge transfer resistance [30,45]. Therefore, MoS 2 -coated steel showed the best performance in corrosion protection, as the corrosion of steel depends on the charge transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the presence or absence of BTA, as shown in Figure 5 and Table 4 , specimen 2 had a lower corrosion current density ( i corr ) and similar or higher E corr compared to specimen 1. Raman and Zhang reported that i corr is decreased and E corr adjusted more toward a positive direction when metal is coated with a graphene or carbon layer [ 35 , 36 ]. They suggested that the carbon layer or graphene reduced the dissolution of metal, thereby decreasing the corrosion rate by 2–3 times, and increased corrosion resistance, thereby moving E corr toward a more positive direction.…”
Section: Resultsmentioning
confidence: 99%
“…CPE1 is the barrier capacitance corresponding to R1 , R ct is the charge transfer resistance, and CPE2 is the capacitance due to the electric double layer generated at the interface between the rust/ barrier and metal substrates. The constant phase element ( CPE ) is a non-ideal capacitance with a varying n , expressed by Equation (2) [ 9 , 25 , 36 , 38 ] where Y 0 is the magnitude of the CPE , and n is a parameter by frequency dispersion. The parameter n is affected by non-homogeneity and surface roughness [ 9 ].…”
Section: Resultsmentioning
confidence: 99%